Diskusi Melalui Peer Group (Teman Sebaya) Terhadap Konsep Diri Remaja Tentang Perilaku Seksual - Rinda Tirta Pratiwi; Fitriani Mediastuti; Winarsih (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: One of factors which influence adolescent self-concept is peer group. The result of Survey Behavior did in 5 town said that 39% respondents had did sexual intercourse when adolescent period at 15-19 years old, 61% at 20-25 years old and 74% adolescent got information about sexuality from their friends. The survey data of married by accident in SMAN 1 Srandakan from year 2007-2008 to 2011-2012 has 15 cases. Influence of peer group happened because adolescent more with friend as a group.Objective: To determine the influence discuss of peer group to adolescent self-concept about sexual behavior in SMAN 1 Srandakan.Methods: The study by Quasi-ekperiment with nonequivalent time sample design. Sampling used simple random sampling of the total respondents 68 students in SMAN 1 Srandakan on March to April 2014. Types of primary data with research instrument using questionnaire. Data analysis used paired t-test.Results: Analysis with paired t-test obtained tcount by -2,130 with significant value 0.037 (p-value<0.05).Conclusion: There is influence discuss of peer group to adolescent self concept about sexual behavior in SMAN 1 Srandakan and statistically meaningful.Keyword: peer group, self concept, sexual behavior, adolescent